THE APPLICATION OF RESPONSIBILITY EDUCATION ON SUSTAINABILITY ISSUES - Tsai, Shieunt-Han; Yang, I-H (International Journal of Application on Economics and Business, 2023)
People start to rethink if to sacrifice the ecology for the prosperity of the various industries for a better life. Responding to the United Nations 2030 Sustainable Development Goal SDGs 4 "Quality Education," in addition to equal education for everyone, its deeper meaning can emphasize the "value-added" of education. Some enterprises and schools in Taiwan are committed to sustainable education, but sustainability issues are often difficult to be understood because of too many terms. Therefore, we divide the topic of sustainable education through game-based learning was conducted that includes three types: Sustainability puzzle, Sustainability and reaction and Sustainability strategy board games. We wish to attract more people to participate in sustainability issues and get a better life.